Femtosecond laser-induced graphene for flexible electronics - Le, Truong-Son Dinh (Nanyang Technological University, 2020)
In 2004, Konstantin Novoselov and Andre Geim discovered graphene and brought that “miracle material” into the real world as the first known two-dimensional (2D) material. The aforementioned discovery has triggered a tremendous amount of research in various fields, including materials science. Graphene is a single layer of sp2-carbon atoms bonded by covalent bonds and organized in a 2D honeycomb lattice. Owing to this arrangement, graphene exhibits extraordinary properties such as excellent mechanical strength, large specific surface area, high electron mobility, great optical transmittance, excellent thermal conductivity, good chemical stability, biocompatibility, and many other supreme properties. All these extraordinary properties are combined in one material make graphene the most promising material to date. So far, graphene has been synthesized via several methods, including mechanical exfoliation, chemical vapor deposition, and liquid-phase exfoliation. However, these methods are multiple-step, time-consuming, and/or incompatible with the device fabrication on flexible and heat-sensitive substrates. Consequently, there is an urgent need for facile and single-step methodologies that can be used for cost-effective and large-scale production of high-quality graphene patterns. Exploration of these novel methodologies may pave the way for the development and commercialization of high-performance graphene-based flexible electronics. The main objective of this research is three-fold: (1) establishment of an effective methodology for the direct fabrication of graphene and its composites on thin, flexible, and heat-sensitive substrates/precursors using femtosecond laser, (2) comprehension of the structures and properties of the produced materials, and (3) development of applications in flexible electronics to demonstrate technological capability.